HARTA DALAM ISLAM (Peran Harta Dalam Pengembangan Aktivitas Bisnis Islami) - Wening Purbatin Palupi (AT-Tahdzib: Jurnal Studi Islam dan Muamalah, 2013)
These days, in society reality around us of ownership of of estae represent standardization indetermining bliss of someone life, estae which abundance indicate that he is child of fortune.So that with assumption, according to economizing writer, enough become a reason why humanbeing of cendrung race to multiply properties estae had, because requirement of human beingor human being easiness to same estae of its position with requirement of human life tochild and or clan. Estae which abundance on earth, before us, basically represent absoluteproperty of Allah of Swt, as creator and power of universe along with its contents. Withunderstanding, of estae which human being have or master only owning role as proxy Allahof swt, to managing it with management mechanism in charge of as according to rule ofthe game which have in Allah nash of swt in Al-Quran and also rule which have teachingRasulullah Muhammad saw, for stock live and life of eternity world.